Log2-x(x+2*logx-3(3-x меньше 0

Log2-x(x+2*logx-3(3-x<0
Гость
Ответ(ы) на вопрос:
Гость
Решение. log(2-x)(x+2)*log(x+3)(3-x) < 0 ОДЗ: x+2 > 0 3-x > 0 2-x > 0 x+3 > 0 2-x не=1 x+3не=1 Рассмотрим неравенства 1. log(2-x)(x+2) > 0=log(2-x)1 {2-x > 1 x > 2 {x+2 > 1 x > -1 -1 < x < 1 {2-x < 1 x > 1 {x+2 < 1 x < -1 нет решений 2. log(2-x)(x+2) < 0=log)2-x)1 {2-x > 1 x < 1 {x+2 < 1 x < -1 x < -1 {2-x < 1 x > 1 {x+2 > 1 x > -1 x > 1 3. log(x+3)(3-x) > 0=log(x+3)1 {x+3 > 1 x > -2 {3-x > 1 x < 2 -2 < x < 2 {x+3 < 1 x < -2 {3-x < 1 x > 2 нет реш 4. log(x+3)(3-x) < 0=log(x+3)1 {x+3 > 1 x > -3 {3-x < 1 X > 2 x > 2 {x+3 < 1 x < -2 {3-x > 1 X < 2 x < -2 вне ОДЗ
Не нашли ответ?
Ответить на вопрос
Похожие вопросы